CHRONIC STRESS AND CORTISOL – MECHANISM OF ACTION AND IMPACT ON THE HUMAN BODY. A REVIEW ARTICLE - Angelika Kędzierska,; Natalia Nafalska,; Krzysztof Feret,; Kamil Kerknawi,; Paulina Mikulec,; Aleksandra Ćwirko-Godycka,; Małgorzata Stopyra,; Dominik Łepecki,; Milena Orzeł,; Aleksandra Bielecka,; Klaudia Forystek, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: In recent years, the negative impact of chronic stress on health and proper functioning of the human body has been increasingly discussed. This phenomenon is a growing problem that affects an increasingly larger part of society. The body's response to stress is the release of cortisol – a glucocorticoid hormone produced in the adrenal cortex, commonly referred to as the "stress hormone." The aim of this article is to analyze the impact of elevated cortisol levels on human organs and systems, as well as to discuss possible preventive measures aimed at reducing chronic stress levels, based on current literature data.State of knowledge: Cortisol is a glucocorticoid hormone produced by the adrenal glands, which plays a crucial role in various physiological processes of the body. Its release is regulated by the hypothalamic-pituitary-adrenal (HPA) axis, a neuroendocrine system responsible for the body's response to stress and maintaining homeostasis. Chronic stress leads to disruptions in the proper regulation of cortisol secretion, which is associated with negative health consequences, such as metabolic disorders, obesity, progression of neurodegenerative diseases, increased risk of cardiovascular diseases, and weakened immune response. Research also indicates a link between elevated cortisol levels and the occurrence of mood disorders, including anxiety and depression.Materials and methodology: Materials and methodology: The review is based on a thorough analysis of materials obtained from scientific databases "PubMed" and "Google Scholar," which serve as verified sources of information.Conclusion: In order to reduce excessive cortisol secretion and its negative effects on the body, it is important to effectively counteract chronic stress. Achieving this goal requires implementing effective coping strategies and lifestyle modifications that can help reduce the frequency of stress in daily functioning.